2020
DOI: 10.21203/rs.3.rs-40261/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Acute Effects of 5 Fluorouracil on Skeletal Muscle Resident and Infiltrating Immune Cells in Mice

Abstract: Abstract Background: 5 fluorouracil (5FU) has been a first-choice chemotherapy drug for several cancer types (e.g. colon, breast, head & neck); however, its efficacy is diminished by patient acquired resistance and pervasive side effects. Leukopenia is a hallmark of 5FU; however, the impact of 5FU-induced leukopenia on healthy tissue is only becoming unearthed. Recently, skeletal muscle has been shown to be impacted by 5FU in clinical and prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…This manuscript has been released as a pre-print at https://www.researchsquare.com/article/rs-40261/v1 ( VanderVeen et al, 2020 ).…”
mentioning
confidence: 99%
“…This manuscript has been released as a pre-print at https://www.researchsquare.com/article/rs-40261/v1 ( VanderVeen et al, 2020 ).…”
mentioning
confidence: 99%
“…The modelling and simulation work presented here is a first attempt to capture the non-linear dose-response of skeletal muscle to cancer chemotherapy treatment. One simplification made was to neglect immune cells, which play significant roles in advancing cachexia by promoting inflammation, and in maintaining muscle homeostasis by regulating cell turnover and coordinating repair and remodelling [51]. Such immune cells are sensitive to chemotherapy treatment and their loss can exacerbate muscle loss and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…85 Recently, it has been demonstrated that chemotherapy reduces the number of skeletal muscle M1-like macrophages and M1-M2-like transitional macrophages but has no effect on M2-like macrophages. 86 These data highlight that dysregulation of the skeletal muscle immune microenvironment may contribute to AML and treatment-related skeletal myopathy and could be a target for prevention/ reversal of cachexia.…”
Section: Myelogenous Cytopenia-related Factorsmentioning
confidence: 91%
“…Monocytes are involved in the transition of pro‐inflammatory M1‐like macrophages, which remove damaged tissue, to anti‐inflammatory and pro‐fibrotic M2‐like macrophages, which mediate extracellular matrix remodelling and skeletal muscle regeneration 85 . Recently, it has been demonstrated that chemotherapy reduces the number of skeletal muscle M1‐like macrophages and M1–M2‐like transitional macrophages but has no effect on M2‐like macrophages 86 . These data highlight that dysregulation of the skeletal muscle immune micro‐environment may contribute to AML and treatment‐related skeletal myopathy and could be a target for prevention/reversal of cachexia.…”
Section: An Opportunity To Waste: Exploring the Multifactorial Contri...mentioning
confidence: 99%